To drill or, not to drill for natural gas in Bangladesh: A comparative economic and reservoir analysis - Khan, Haniyum Maria; Rahman, Mohammad Moshiur; Khandaker, Nadim R. (Journey for Sustainable Development and Peace Journal, 2023)
With the growing population, Bangladesh is struggling to provide energy to meet the demands of energy-dependent sectors. Bangladesh has a total of 28 gas fields which are lagging in terms of production and fulfilling national demand. The government of Bangladesh has decided to import liquified natural gas (LNG) from the international market to pace up its energy supply. Being subjected to a highly volatile market, LNG prices are unstable and quite high compared to other natural gas alternatives. This paper examines to what extent the economic investments vary between LNG import and drilling for natural gas within Bangladesh. It also analyzes the reservoir types and characteristics of potential hydrocarbon reservoirs in both onshore and offshore Bangladesh to evaluate the prospect of future drillings. The cost analysis estimates that the price of LNG import will be 14 times higher than exploring for and producing from domestic hydrocarbon resources and reserves respectively till 2030. Even in a situation with fewer (than expected) resources in the unexplored potential zones of the country, future investments in new reserves will still be profitable for the long-term development of the energy sector in Bangladesh.